Diagnosis and management of diaphragmatic pericardial hernia: A case report (International Seven Journal of Health Research, 2023)
Introduction: Diaphragmatic hernias can be congenital or acquired. Congenital diaphragmatic hernia is a relatively common malformation and can be diagnosed in the prenatal period using ultrasound. After birth, computed tomography is the most accurate diagnostic test and helps to assess the anatomical relationships between the viscera. Traumatic diaphragmatic hernia (TDH) is characterized by the passage of part of the abdominal contents into the thoracic cavity through trauma to the thoracoabdominal transition. Pericardial diaphragmatic hernia is a direct communication between the pericardium and the peritoneal cavity, through a defect in the diaphragm. It can be congenital or associated with diaphragmatic rupture after trauma. Case presentation: V.B, 57, complaining of chronic constipation, presented with hiatus hernia on chest X-ray and CT scan. The images showed herniation of fat content and intestinal loops into the chest through the anteromedial wall of the left hemidiaphragm, compressing the medial aspect of the lingula, with no evidence of complications. On April 6, 2023, she underwent diaphragmatic herniorrhaphy via the thoracic route. She returned for post-operative follow-up complaining of nausea, vomiting and asthenia. A new total abdominal tomography scan showed the presence of an anterior diaphragmatic hernia on the left. Subsequently, she underwent a thoracic surgical approach with a proposal to correct the diaphragmatic hernia. However, an inventory of the cavity revealed plication of the lateral diaphragm without herniation points. The decision was therefore made to open the pericardium, showing a diaphragmatic pericardial hernia, with a 0.5 cm ring containing the epipelon, transverse colon and stomach in the pericardium. Adhesions were lysed and the contents returned to the abdominal cavity. The patient evolved satisfactorily in the postoperative period. Discussion: Both diaphragmatic hernia and pericardial diaphragmatic hernia can be serious and require immediate medical intervention. They are rare pathologies that can be confused with other respiratory or cardiac diseases, making it difficult for doctors to diagnose them. Surgery is necessary to repair the hernia and reduce the risk of complications, which increase over time. Final considerations: In this case report, we have highlighted the complexity and importance of early and accurate diagnosis of diaphragmatic hernias, including the rare pericardial diaphragmatic hernia. Diaphragmatic hernia, whether congenital, acquired through trauma or associated with diaphragmatic rupture, can result in painful complications if not recognized and controlled. The clinical situation presented in this case, in which a pericardial diaphragmatic hernia was identified during the postoperative period of a thoracic diaphragmatic hernia, highlights the importance of continuous surveillance after surgical intervention.